Analytical Investigation of the Limits for the In-Plane Thermal Conductivity Measurement Using a Suspended Membrane Setup - Linseis, Vincent; Voelklein, F.; Reith, Heiko; Woias, P.; Nielsch, Kornelius (Journal of Electronic Materials, 2018)
An analytical study has been performed on the measurement capabilities of a 100-nm thin suspended membrane setup for the in-plane thermal conductivity measurements of thin film samples using the 3ω measurement technique, utilizing a COSMOL Multiphysics simulation. The maximum measurement range under observance of given boundary conditions has been studied. Three different exemplary sample materials, with a thickness from the nanometer to the micrometer range and a thermal conductivity from 0.4 W/mK up to 100 W/mK have been investigated as showcase studies. The results of the simulations have been compared to a previously published evaluation model, in order to determine the deviation between both and thereby the measurement limit. As thermal transport properties are temperature dependent, all calculations refer to constant room temperature conditions.
CRIS-Team Scopus Importer:2022-04-14
Keywords: in-plane; nanostructures; seebeck coefficient; resistivity; thermal conductivity; thermoelectrics; Thin film characterization; ZT